International handbook of media literacy education - Lee, Alice Y.L.; De Abreu, Belinha S.; McDougall, Julian; Melki, Jad; Mihailidis, Paul (Routledge, 2017)
At the forefront in its field, this Handbook examines the theoretical, conceptual, pedagogical and methodological development of media literacy education and research around the world. Building on traditional media literacy frameworks in critical analysis, evaluation, and assessment, it incorporates new literacies emerging around connective technologies, mobile platforms, and social networks. A global perspective rather than a Western-centric point of view is explicitly highlighted, with contributors from all continents, to show the empirical research being done at the intersection of media, education, and engagement in daily life. Structured around five themes?Educational Interventions; Safeguarding/Data and Online Privacy; Engagement in Civic Life; Media, Creativity and Production; Digital Media Literacy?the volume as a whole emphasizes the competencies needed to engage in meaningful participation in digital culture.